UTILIZATION OF TANNERY SHAVING WASTE FOR MANUFACTURING SYNTHETIC LEATHER - Naimah Putri; Ratri Retno Utami (Politek ATK Yogyakarta Press, 2024)
Reusing leather waste is a global challenge in leather processing industry. Utilizing shaving leather waste using cost-effective mechanical methods can be used. Shaving waste is used as a filler for Polyvinyl Chloride (PVC) based synthetic leather. The amount of shaving waste used was varied, f1: 8%, s2: 15%, and f3: 20%. This research was conducted to determine the characteristic of synthetic leather derived from shaving leather waste including organoleptic and mechanical properties. The research method was carried in three stages, first was preparation, second was formulation, and third was testing. Testing is carried out based on the Indonesian National Standard (SNI) 1294;2009. The organoleptic results showed that there were no bubbles, cracks, wrinkles, and stains. The tensile strength values at f1, f2, and f3 were 10,433, 6,614, and 5,557N/mm2. The longitudinal tear strength values f4, f8, dan f12 were 25,972, 42,285, and 58,807N while the transverse tear strength values were 20,197N for f4, 38,009N for f8, and 54,288N for f12. The elongation test results for f4, f8, dan f12 were 54,862, 44,588, and 42,523% respectively. The addition of shaving waste of 8%, 15%, and 20% provides synthetic leather conditions that meet organoleptic and elongation standard. Meanwhile, the tensile strength and tear strength does not meet SNI because there was influence from composition/formulation on of other additives.